TANGGUNGJAWAB LIKUIDATOR KEPADA PEMEGANG SAHAM DALAM LIKUIDASI PERSEROAN PT. RAHMAN TAMIN: (Studi Tentang Penetapan Penggantian Likuidator PT. Rahman Tamin Berdasarkan Putusan Mahkamah Agung RI No. 2660 K/Pdt/2014 Juncto Penetapan No. 110/Pdt.P/2014/Pn.Jkt.Bar) - Martry Gilang Rosadi (Program Magister Ilmu Hukum Universitas Ekasakti, 2020)
At the time of PT.Rahman tamin dissolved and appointed liquidator to clinch wealth the company had not yet there is a duty and responsibility that conducted by a liquidator tothe new liquidator by decisions of the supreme court to the court appointing him, Thus causing shareholders suffer losses.The research is normative. legal researchThe data used is the primary law, secondary and tertiary.PT. Rahman Tamin in likuidatioan namely by making it in the form of cash or liquid in order to be distributed to shareholders, a team of the liquidator Pt.Rahman tamin is in liquidation discharge of obligations in accordance with the provisionsact of limited company. Responsibility liquidator appointed the team liquidator in liquidation have carried out in accordance withact. But the fact that is found in the trial based on considerations judge through west jakarta district court decision number110/PDT.P/2014/PN.Jkt.BarStated that withto misuse the authority conducted by among the very cause of the liquidator before the turn of the liquidator is in liquidation PT .Rahman Tamin.The liquidator PT .Rahman Tamin formerly wo not submit the funds that have been given by a prospective buyersby reason of these is direct to the court .